2015
DOI: 10.1073/pnas.1508990112
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation induces dermal Vγ4 + γδT17 memory-like cells that travel to distant skin and accelerate secondary IL-17–driven responses

Abstract: Gamma delta (γδ) T cells represent a major IL-17 committed T-cell population (γδT17 cells) in the mouse dermis. Following exposure to the inflammatory agent imiquimod (IMQ) the Vγ4 + subset of γδT cells produce IL-17 in the skin and expand rapidly in draining lymph nodes (LNs). Local IMQ treatment in humans is known to exacerbate psoriasis skin lesion activity at distant sites. Whether expanded γδT17 cells sensitize distant sites to inflammation has been unknown. Here we show that expanded Vγ4 + γδT17 cells eg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
193
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(215 citation statements)
references
References 40 publications
16
193
1
Order By: Relevance
“…It has recently been suggested that naive (uncommitted) gd T cells are continuously produced from embryonic day 16 and, upon recognition of the "model Ag" PE, might be able to initiate IL-17 production without prior commitment to the gdT17 lineage in the thymus (30,43 Ag-specific system (4) and in a recent study, CD3g and CD3d double haploinsufficient mice, which exhibit decreased signaling strength downstream of the TCR, lose a large fraction of their IFN-g-producing gd T cells during embryonic development, which is sustained during adulthood (44). TCR-Vg4 + gd T cells expand during imiquimod-induced skin inflammation and redistribute to previously noninflamed skin sites where they were more responsive to IL-1b than nonimiquimodsensitized gdT17 cells due to higher expression of IL-1R1 (45). The readily inducible expression of Il1r1 in TCR-Vg4 + gd T cells in a TCR-dependent or TLR1-or TLR2-dependent (46) manner, and thus the direct engagement of the Vg4 + gd-TCR by ligands in the inflamed skin, might explain their exquisite responsiveness to IL-1b plus IL-23 and subsequently result in the preponderance of TCR-Vg4 over TCR-Vg6 in induced gdT17 cells in vivo as compared with their in vitro-induced counterparts.…”
Section: Discussionmentioning
confidence: 98%
“…It has recently been suggested that naive (uncommitted) gd T cells are continuously produced from embryonic day 16 and, upon recognition of the "model Ag" PE, might be able to initiate IL-17 production without prior commitment to the gdT17 lineage in the thymus (30,43 Ag-specific system (4) and in a recent study, CD3g and CD3d double haploinsufficient mice, which exhibit decreased signaling strength downstream of the TCR, lose a large fraction of their IFN-g-producing gd T cells during embryonic development, which is sustained during adulthood (44). TCR-Vg4 + gd T cells expand during imiquimod-induced skin inflammation and redistribute to previously noninflamed skin sites where they were more responsive to IL-1b than nonimiquimodsensitized gdT17 cells due to higher expression of IL-1R1 (45). The readily inducible expression of Il1r1 in TCR-Vg4 + gd T cells in a TCR-dependent or TLR1-or TLR2-dependent (46) manner, and thus the direct engagement of the Vg4 + gd-TCR by ligands in the inflamed skin, might explain their exquisite responsiveness to IL-1b plus IL-23 and subsequently result in the preponderance of TCR-Vg4 over TCR-Vg6 in induced gdT17 cells in vivo as compared with their in vitro-induced counterparts.…”
Section: Discussionmentioning
confidence: 98%
“…Depending on the context, the same effector functions that make γδ T cells an important arm of the immune system can alternatively contribute to the development, progression and exacerbation of various diseases. These harmful effects include roles in the pathogenesis of autoimmune conditions such as psoriasis, multiple sclerosis, and arthritis, as well as contributions to breast cancer metastasis and bone loss 37 . Given that the beneficial and deleterious effects of γδ T cells are largely attributable to the ability of these cells to rapidly produce high levels of inflammatory cytokines, it is important to understand the development and function of the major effector subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that Vg4 + Vd4 + CD27 2 cells preferentially accumulate in the muscle in EAM-induced mice. It has been reported that Vg4 + Vd4 + cells produce IL-17 and are involved in the development of collagen-induced arthritis (40) and psoriasis-like skin changes (41)(42)(43). By using intracellular cytokine staining, we found that the most of GM-CSF-producing gdT cells in the draining LNs and the muscle in EAM-induced mice were Vg4 + Vd4 + cells (Fig.…”
Section: Vd4mentioning
confidence: 59%